2005
DOI: 10.2337/diacare.28.8.1995
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Resistance and Preeclampsia in Gestational Diabetes Mellitus

Abstract: OBJECTIVE -To compare the degree of insulin resistance in women with gestational diabetes mellitus (GDM) who do and do not develop preeclampsia.RESEARCH DESIGN AND METHODS -We conducted a prospective cohort study of initially normotensive women with GDM who underwent oral glucose tolerance tests (OGTTs), intravenous glucose tolerance tests (IVGTTs), and glucose clamp studies in the early third trimester (n ϭ 150) and 15 months postpartum (n ϭ 89). After delivery, the women were categorized as nonpreeclamptic o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 38 publications
1
35
0
3
Order By: Relevance
“…Women with insulin-dependent diabetes antedating pregnancy are known to have an increased risk of hypertension in pregnancy, 27 but these women primarily have insulin deficiency rather than insulin resistance, and they often have renal dysfunction that might underlie blood pressure elevation. More recently, risk of hypertension in pregnancy has been reported by some, 18,[28][29][30][31] although not all 32,33 investigators to be increased among women with gestational diabetes, a disorder associated with underlying insulin resistance. 34 Some, 31,35 but not other, 18 studies have suggested a relation between less-striking degrees of glucose intolerance and subsequent hypertension in pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Women with insulin-dependent diabetes antedating pregnancy are known to have an increased risk of hypertension in pregnancy, 27 but these women primarily have insulin deficiency rather than insulin resistance, and they often have renal dysfunction that might underlie blood pressure elevation. More recently, risk of hypertension in pregnancy has been reported by some, 18,[28][29][30][31] although not all 32,33 investigators to be increased among women with gestational diabetes, a disorder associated with underlying insulin resistance. 34 Some, 31,35 but not other, 18 studies have suggested a relation between less-striking degrees of glucose intolerance and subsequent hypertension in pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Insulin resistance is also recognized as a key mechanism in type 1 diabetes mellitus [16,17]. Similarly, in pregnant patients, insulin resistance can escalate, especially when associated with other factors that lead to the development of PIH, GDM, or both [9].…”
Section: Introductionmentioning
confidence: 99%
“…Pregnant women with GDM have been shown in population studies to have increased risk of PIH compared with nondiabetic patients, and pregnant patients with hypertension (especially if obese) are at increased risk for developing GDM during the pregnancy [6,7]. It has been hypothesized that this association, at least in part, could be due to insulin resistance, which is a physiologic phenomenon and adaptation in normal pregnancy but that in the predisposed individual with other risk factors could lead to pathologic processes (ie, hyperinsulinemia), such as the development of PIH, GDM, or both [8][9][10]. Insulin resistance increases in severity during gestation [10] and becomes prominent in the late second and third trimesters [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…GH has been associated with hyperinsulinemia [2,9,10,11,12,13]. No similar associations were reported regarding the relationship between PE and IR either in normoglycemic pregnancies or in GDM [14,15,16,17,18,19]. PE is associated with a failure in the trophoblast invasion of the spiral arteries of the placenta, and it may lead to impaired uteroplacental perfusion and to the release of several vasoactive factors into maternal circulation that finally cause endothelial dysfunction, vasoconstriction and hypertension [20].…”
Section: Introductionmentioning
confidence: 99%